Crystallization properties of Sb-rich GeSbTe alloys by in-situ morphological and electrical analysis. (July 2017) - D'Arrigo, G.; Mio, A.M.; Boniardi, M.; Redaelli, A.; Varesi, E.; Privitera, S.; Pellegrino, G.; Spinella, C.; Rimini, E.
Abstract: Phase Change Memory (PCM) operation relies on the reversible transition between two stable states (amorphous and crystalline) of a chalcogenide material, mainly of composition Ge2 Sb2 Te5 (GST). In Wall type PCM cells, cycling endurance induces a gradual change of the cell electrical parameters caused by variations in the chemical composition of the active volume. The region closer to the GST-heater contact area, becomes more Sb rich and Ge depleted. The new alloy has usually different thermal characteristics for the phase transitions that influence the electrical behavior of the cell. In this study we analyze the morphological, structural and electrical properties of two Sb-rich non-stoichiometric alloys: Ge14 Sb35 Te51 and Ge14 Sb49 Te37, at their amorphous and crystalline phase. Experiments have been performed in non-patterned blanket films and, to simulate the device size, in amorphous regions of 20 nm, 50 nm and 100 nm diameter respectively. The amorphous Ge14 Sb35 Te51 film crystallizes in the meta-stable face centered cubic structure at 150 °C and in the rhombohedral phase at 175 °C, behavior characteristic of the Ge1 Sb2 Te4 composition. The average grain size is of about 100 nm after an annealing at 400 °C. The Ge14 Sb49 Te37 film crystallizes only in the hexagonal phase, with an average grain size of about 60 nm after annealing at 400 °C. The X-ray fluorescence analysis shows a non uniform distribution of the constituent atoms and in particular a Ge signal decrement and a Sb enrichment at grain boundaries. The in situ annealing of amorphous nano-areas (RESET state under a thermal stress) indicates a fast re-crystallization speed for Ge14 Sb35 Te51, 80 pm/s at 90 °C, and a lower speed for Ge14 Sb49 Te37, at 130 °C a grain growth velocity of 50 pm/s has been measured. The different behavior of the two alloys is discussed in terms of structural vacancies filling by the Sb atoms in excess and by their segregation at grain boundaries. The influence of the obtained results on the device characteristics is discussed.